Rupture of the anterior cruciate ligament and tennis: Clinical symptoms, etiology and epidemiology - Le Goux, P.; Blondeau, J. M. (2001)
The anterior cruciate ligament (ACL) rupture is relatively uncommon among tennis players. A study conducted in Grenoble found only 13 cases of ACL rupture in a total of 272 acute tennis injuries seen in an accident and emergency department over a period of 10 years. Nevertheless, this injury is still very interesting to study in more detail.